2012
DOI: 10.4155/bio.12.42
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Lc–MS/MS Quantification of The Major Benzodiazepines And Their Metabolites on Dried Blood Spots Using A Simple And Cost-Effective Sample Pretreatment

Abstract: The presented strategy proved to be efficient for the rapid analysis of the selected drugs. Indeed, the offline sample preparation was reduced to a minimum, using a small amount of organic solvent and consumables, without affecting the accuracy of the method. Thus, this approach enables simple and rapid DBS analysis, even when using a non-DBS-dedicated autosampler, while lowering the costs and environmental impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…The current analysis did not take into account investments required for developing a DBS method, which may be more costly than plasma method development. On the other hand, several approaches have been made to speed-up the analytical method such as automated flow-through desorption or reduced sample pre-treatment resulting in a cost-effective analytical method[22, 23]. These technical innovations will further reduce analysis costs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis did not take into account investments required for developing a DBS method, which may be more costly than plasma method development. On the other hand, several approaches have been made to speed-up the analytical method such as automated flow-through desorption or reduced sample pre-treatment resulting in a cost-effective analytical method[22, 23]. These technical innovations will further reduce analysis costs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from one recent study by Déglon et al (which determined clobazam and clonaxepam) [23], no recent publication reported on the simultaneous determination of the concentration of multiple AEDs in a single DBS sample. The combined determination of different AEDs has the potential to monitor polymedicated patients and offers the possibility to quantify clinical samples of patients treated with any of these compounds in one sequence, with a single set of calibrators and QC samples [24].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on concurrent monitoring of multiple AEDs from one DBS were done mostly with high performance liquid chromatography (HPLC) and included whole blood concentrations of AEDs such as carbamazepine, phenytoin, lamotrigine and barbiturates with limited clinical validation [13], [14]. Recently, a group in North Ireland published a detailed HPLC ultraviolet method for concurrent determination of carbamazepine (CBZ) and its active metabolite carbamazepine-10,11 epoxide (CBZE), levetiracetam (LEV), lamotrigine (LTG) and phenobarbital (PHB) in DBS of children [15].…”
Section: Introductionmentioning
confidence: 99%